Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.20524/aog.2017.0211
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of incidental pancreatic cyst on upper endoscopic ultrasound

Abstract: Background:This study aimed to determine the prevalence of incidental pancreatic cysts in patients undergoing upper endoscopic ultrasound without a known pancreatic abnormality.Methods:This prospective study was conducted in two hospitals in Spain and enrolled consecutive patients referred for upper endoscopic ultrasound for a condition unrelated to the pancreas. Patients with a previous pancreatic anomaly, history of acute or chronic pancreatitis, evidence of acute pancreatitis, previous upper gastrointestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…In the meta-analysis of Zerboni G, et al in 2019, prevalence of PCLs in asymptomatic individuals was 8 % [23], while incidence of these lesions increases with age and reaches 37 % in patients older than 80 [24]. In Spain, a prospective study performed in 298 patients, the authors recorded that incidental prevalence of pancreatic cysts on EUS (21.5 %) was higher than prevalence estimates in cross-sectional imaging studies [6]. Surgery is currently considered the standard of care for malignant and highrisk premalignant PCLs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the meta-analysis of Zerboni G, et al in 2019, prevalence of PCLs in asymptomatic individuals was 8 % [23], while incidence of these lesions increases with age and reaches 37 % in patients older than 80 [24]. In Spain, a prospective study performed in 298 patients, the authors recorded that incidental prevalence of pancreatic cysts on EUS (21.5 %) was higher than prevalence estimates in cross-sectional imaging studies [6]. Surgery is currently considered the standard of care for malignant and highrisk premalignant PCLs.…”
Section: Discussionmentioning
confidence: 96%
“…Magnetic resonance imaging and magnetic resonance cholangiopancreatography are superior to computed tomography in identifying communication between a PCL and the pancreatic duct, the number of PCLs, and presence of a mural nodule [5]. In Spain, a prospective study performed in 298 patients showed that prevalence of unexpected PCLs on endoscopic ultrasound (EUS) is 21.5 %, higher than the prevalence estimates in cross-sectional imaging studies [6]. Currently, the management of PCLs relies on the combination of clinical features, cross-sectional imaging and endoscopic ultrasound with or without fine-needle aspiration (FNA) and fluid analysis.…”
Section: %)mentioning
confidence: 99%
“…The reported prevalence rates for pancreatic cysts have varied depending on the imaging method used for detection. Namely, the reported detection rates have been for 2.2%-2.6%[17,18] for computed tomography (CT), 3.5%[19] for US, 10%-44.7%[10,16,18,20-22] for MRI, and 9.4%-21.5%[23,24] for endoscopic ultrasonography (EUS). A similar amount of reports[10,14,16,17,19-21,23,24] have demonstrated aging as a significant risk factor for pancreatic cysts; in general, the frequency of pancreatic cysts among the elderly is over 20%.…”
Section: Prevalence Of Pancreatic Cystsmentioning
confidence: 99%
“…Looking at cross-sectional imaging studies on general population, the prevalence of pancreatic cyst widely ranges between 2.4% and 49% with a mean value estimated in about 12%[ 5 6 7 8 9 10 11 12 13 14 15 ] [ Table 1 ]. This impressive number becomes even more clinically significant, considering that only about 1% of patients have a cyst >2 cm.…”
Section: Lessons From Epidemiological Studiesmentioning
confidence: 99%